Application of seismic methods for siting of radioactive waste repositories in crystalline rock - Juhlin, Christopher; Cosma, C.; Heikkinen, E. (2008)
High resolution reflection seismic surveying has proven useful for locating fracture zones in crystalline rock and has become a key tool for siting of potential high-level nuclear waste repositories. We present here results from 3 site investigations that we have been involved in at locations in Sweden and Finland. Both Sweden and Finland plan on storing their waste at depths of 400-700 m in crystalline rock and it is, therefore, of particular interest to obtain high resolution images in the depth interval 0-1000 m. Results from these seismic investigations, together with borehole data, have played an important role in defining which parts of the rock mass are suitable for a repository at the 3 sites.